An Overview Of Learning Support Factors On Mathematic Games - Ahmad Fairuzabadi; Ahmad Afif Supianto (Universitas Muhammadiyah Malang, 2019)
In this study, we examined the factors in game design that were used by developers to support the interests of mathematics learning. The aim is to overcome the lack of empirical evidence about the impact of factors in the game on learning outcomes, identify how the design of in-game activities affects learning, and develop an overview of general recommendations for designing mathematics education games. This study tries to illustrate the impact of game design factors in mathematics education games on the objectives and results of game-based learning.